1987
DOI: 10.1007/bf00413255
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein and calcium in stratum corneum cell cohesion

Abstract: The work reported here indicates that protein and calcium have roles in stratum corneum cell cohesion. A zwitterionic surfactant, 6-octadecyldimethyl ammoniohexanoate (C18AH), was found to completely disaggregate pig and human stratum corneum into intact, individual cells. This method of disaggregation provided a tool to determine the role of tissue components in cell cohesion. The C18AH disaggregation of pig and human stratum corneum was accelerated by proteolytic enzyme and ethylenediaminetetraacetate (EDTA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…However, detergent extraction studies have shown that not only CD, but also extracellular lipids regulate SC cohesion [117,119]. We have applied the term SC 'integrity' as a measure of resistance to the dissociation of adjacent corneocytes, quantified as the number of D-Squame ® tape strippings required to raise the transepidermal water loss to defined levels (e.g.…”
Section: Sc Integrity/cohesionmentioning
confidence: 99%
“…However, detergent extraction studies have shown that not only CD, but also extracellular lipids regulate SC cohesion [117,119]. We have applied the term SC 'integrity' as a measure of resistance to the dissociation of adjacent corneocytes, quantified as the number of D-Squame ® tape strippings required to raise the transepidermal water loss to defined levels (e.g.…”
Section: Sc Integrity/cohesionmentioning
confidence: 99%
“…In order to determine whether the 40-kilodalton glycoprotein molecule can persist whole in the degradative environment of the stratum corneum or whether it may be partially cleaved but yet recognized by the antibody, we have exposed desquamin to several pro téinases that are routinely used to generate peptide maps, at concentrations that are typically used for that purpose. Trypsin has been reported to promote squame disso ciation of isolated stratum corneum [7,9], When we reacted desquamin with trypsin ( fig. la-e), we found that it was resistant to proteolytic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…In the early 90 th , emerging data suggested that the lipids, crucial for the barrier's impermeability, played only a limited part in tissue cohesion, whereas the integrity of the SC depended mostly on the corneocytes and associated intercellular junctions. In particular, the finding that protease activity was necessary for desquamation to take place [1,2], as well as the identification of corneodesmosin (CDSN) as the only protein specifically localized in the extracellular part of corneodesmosomes [3], the modified desmosomes in the SC, contributed to reconsider the place of proteins in the barrier function of the SC.…”
Section: Introductionmentioning
confidence: 99%